2023
DOI: 10.1039/d3cc02523c
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalyzed regioselective rollover dual C–H annulation cascade: facile approach to phenanthrene derivatives

Abstract: Annulations of unsaturated systems through C-H activation represent a powerful tool for multi cyclic scaffolds. Having co-ordinating centers in both annulation partners, a dual coordination strategy, would afford remarkable selectivities...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…There is a reasonable number of reports on the individual synthesis of phenanthrenes [16][17][18][19][20][21] and pyrazoles. [22][23][24][25][26] For instance, the research group of Wang demonstrated the efficient formation of phenanthrols starting from diphenyl dicarbonyls and tosyl hydrazide under basic conditions (Scheme 1a).…”
mentioning
confidence: 99%
“…There is a reasonable number of reports on the individual synthesis of phenanthrenes [16][17][18][19][20][21] and pyrazoles. [22][23][24][25][26] For instance, the research group of Wang demonstrated the efficient formation of phenanthrols starting from diphenyl dicarbonyls and tosyl hydrazide under basic conditions (Scheme 1a).…”
mentioning
confidence: 99%